PENGARUH STRES KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PERAWAT DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA MASA PANDEMI COVID-19 (STUDI PADA RSUD DR. H. CHASAN BOESOIRIE TERNATE) - Tuahuns, Vikram B; Soleman, Marwan Man; Husen, Zulaiha (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2023)
bjectives: The objectives of this study were: (1) To determine the effect of work stress on the performance of nurses at RSUD Dr. H. Chasan Boesoirie Ternate; (2) To determine the effect of the work environment on performance; (3) To determine the effect of the work environment on job satisfaction; (4) To determine the effect of job stress on job satisfaction; (5) To determine the effect of job satisfaction on performance; (6) To determine the effect of work stress on nurse performance mediated by job satisfaction; and (7) to determine the effect of the work environment on nurse performance mediated by job satisfaction. The number of research samples was 83 nurses.Methodology: The test tool used is SmartPLS 3.0 as a statistical test tool.Findings: The second, third, fifth, and seventh hypotheses are accepted because the statistical t value is greater than t table, and the p value is smaller than alpha 0.05. While the first, fourth and sixth hypotheses were rejected because the p-value was greater than 0.05.Conclusion: The results of this study indicate that: (1) Job stress has no effect on the performance of nurses at RSUD Dr. H. Chasan Boesoirie Ternate; (2) work environment has a significant effect on performance; (3) work environment has a significant effect on job satisfaction; (4) Job stress has no effect on job satisfaction; (5) Job satisfaction affects performance; (6) Job stress has no effect on nurse performance mediated by job satisfaction; and (7) work environment influences nurse performance mediated by job satisfaction.